Upaya Meningkatkan Partisipasi Mahasiswa Melalui Analisis Perencanaan Pembelajaran Berbasis Problem Based Learning Oleh Dosen PPKn - Kemil Masi , Thomas; Moy, Maria G.; Aeng Lau, Clarisa A.; Keraf, Veronika Tiara Hingi (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the implementation of learning planning by civics teachers, identify effective strategies in efforts to increase student participation through analysis of problem-based learning planning by civics teachers, and describe the supporting and inhibiting factors in the process. The study uses a qualitative method with a descriptive research type. Qualitative research is a type of research that produces data in the form of words rather than numbers. Qualitative research aims to understand phenomena experienced by research subjects in the field, such as behavior and perceptions holistically, in the form of descriptions using words and language. The results of the study show that Civic Education lecturers develop structured learning plans by compiling comprehensive Semester Learning Plans (RPS) using the PBL learning model, which is specific, contextual, and participatory (e.g., case discussions, interactive games). In this case, lecturers can also create a safe and critical thinking classroom environment [da2.1]. The PPKn lecturers' Problem-Based Learning-based learning plans have been implemented systematically and effectively in increasing student participation. The clarity of the RPS, the use of contextual learning strategies, and the creation of a safe classroom environment are the main factors supporting student involvement.